Haptic visual and superimposed digital imaging analysis improves the interrater reliability of J-sign assessment in patients with patellofemoral instability: a prospective diagnostic study - Zimmermann, Felix; Mandelka, Eric; Gierse, Jula; Grützner, Paul Alfred; Vetter, Sven Y.; Balcarek, Peter (Journal of Clinical Medicine, 2025)
Background: J-sign assessment is increasingly important for decision-making in patients with patellar instability. However, the low interrater reliability of the J-sign evaluation has raised concerns. The aim of this study was to investigate whether haptic visual assessment or superimposed digital imaging analysis might improve interrater reliability. Methods: In 51 patients with ≥ 1 patellar dislocation, J-sign grading was assessed by two experienced observers via three different methods: (i) plain visual evaluation; (ii) combined haptic visual assessment, including palpation of the medial and lateral patellar facets with the thumb and index finger during active knee joint motion; and (iii) a digital photo application tool using superimposed digital imaging analysis obtained at 90° of flexion–knee joint flexion and full extension. Results: For the visual assessment of the J-sign, the interrater reliability was fair, with κ = 0.39 ± 0.11 [0.18–0.6]. The interrater reliability of the haptic visual assessment and the photo application reached a good level of agreement, with κ = 0.89 ± 0.05 [0.8–0.98] and κ = 0.85 ± 0.05 [0.74–0.95], respectively. Conclusions: Plain visual evaluation of the J-sign revealed fair interrater reliability. The haptic visual assessment of the J-sign and the digital photo application tool yielded good interrater reliability. The results indicate that haptic visual assessment of J-sign should be implemented in daily clinical practice and used to communicate findings between and among physicians and studies.